RETRACTED: Designing a professional request of the regional farming community for information-analytical, consulting and research services of agricultural education - Aydinova Angelika; Cherepukhin Timofey; Isaenko Alexander; Chvalun Roza; Ivashova Valentina (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001